2016
DOI: 10.1369/0022155416672210
|View full text |Cite
|
Sign up to set email alerts
|

Megalin Is Predominantly Observed in Vesicular Structures in First and Third Trimester Cytotrophoblasts of the Human Placenta

Abstract: SummaryThe membrane receptor megalin is crucial for normal fetal development. Besides its expression in the developing fetus, megalin is also expressed in the human placenta. Similar to its established function in the kidney proximal tubules, placental megalin has been proposed to mediate uptake of vital nutrients. However, details of megalin expression, subcellular localization, and function in the human placenta remain to be established. By immunohistochemical analyses of first trimester and term human place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
0
13
0
1
Order By: Relevance
“…It is still unknown why albumin and IgG are transported differently, but involvement of other albumin receptors could be part of the explanation. For example, megalin and cubilin (Box 4) have been found to be expressed in the placenta (159161), and it has been suggested that they might facilitate retrograde recycling of albumin back to the maternal circulation (159).…”
Section: Functional Consequence Of Fcrn Expression In Epitheliummentioning
confidence: 99%
“…It is still unknown why albumin and IgG are transported differently, but involvement of other albumin receptors could be part of the explanation. For example, megalin and cubilin (Box 4) have been found to be expressed in the placenta (159161), and it has been suggested that they might facilitate retrograde recycling of albumin back to the maternal circulation (159).…”
Section: Functional Consequence Of Fcrn Expression In Epitheliummentioning
confidence: 99%
“…This Cd redistribution could be explained by MT redistribution, since they observed the same pattern with MT levels during this time of gestation [ 47 , 64 ]. Placenta has been showed to highly express megalin in cytotrophoblasts during first and third trimester [ 65 ]: megalin is a transmembrane receptor which mediates uptake and trafficking of many ligands including MT in kidney and other tissues [ 66 , 67 , 68 ]. However, other transporters that participate in receptor-mediated endocytosis of MT could be also involved [ 69 , 70 ].…”
Section: Cadmium Distribution During Pregnancymentioning
confidence: 99%
“…Using in vivo models, Cd exposure has been associated to preeclampsia development with increased systolic pressure and proteinuria [ 72 , 73 , 74 ]. The mechanisms suggested for preeclampsia induction by Cd exposure are: placental damage caused by oxidative DNA damage [ 65 , 72 ], and high levels of corticosterone in plasma, consequence of placental alterations (downregulation of 11β-hydroxysteroid dehydrogenase, 11β-HSD2) [ 73 , 75 ]. Other mechanisms possibly related to the development of preeclampsia are immunological disorders.…”
Section: Toxic Effects In Damsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, megalin mediates reabsorption of filtered plasma proteins, rescuing vital nutrients from urinary excretion 7. Besides the kidney, megalin is also expressed in a number of other specialized epithelia throughout the body including type II pneumocytes of the lung, the choroid plexus epithelium, and placental cytotrophoblasts 811. Notably, megalin is also expressed in the non-pigmented ciliary body epithelium as well as the RPE in the adult mammalian eye 10,12,13…”
mentioning
confidence: 99%